A structurationist analysis of differing policies oriented to the pharmaceutical industry: Turkey and Brazil - (:unkn) unknown (IGI Global, 2014)
This chapter has two purposes closely related to each other. The first one is to analyze why countries that have similar characteristics and benefits to each other develop different strategies in terms of rules that regulate the intellectual property rights in the pharmaceutical industry. The second one is to analyze the factors that determine active participation in global governance processes with regards to the intellectual property rights of countries that are developing, specifically in the pharmaceutical industry. The study used the structurationist approach developed by John M. Hobson, and findings were tested by comparing the examples of two countries: Turkey and Brazil. © 2014 by IGI Global. All rights reserved.